Use of stable isotopes of carbon to detect coconut water adulteration - Imaizumi, Vitor Massami [UNESP]; Pereira Sartori, Maria Marcia [UNESP]; Ducatti, Carlos [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (Univ Sao Paolo, 2019)
Industrialized coconut water may have been adulterated by adding sugar above the limit permitted by law. According to Brazilian law, industrialized coconut water can receive the maximum addition of 1 g of sugar per 100 mL of the drink. This work aimed to detect adulteration in industrialized coconut water produced in Brazil and measure the relative isotopic enrichment in fresh coconut water, using the techniques of stable isotopes of carbon. Fresh coconut water samples from 13 locations, industrialized coconut water samples of 17 different brands and cane sugar were analyzed by Isotope Ratio Mass Spectrometer coupled to an elemental analyzer. The relative isotopic enrichment found for fresh coconut water samples ranged from -26.40 to -23.76. From 17 brands of coconut water analyzed, 11 were adulterated by excess sugar and two were already adulterated by presenting soluble solids content higher above the threshold permitted by law. In 65 % of Brazilian industrialized coconut water, the amount of exogenous sugar is higher than the limit permitted by law. Most Brazilian companies do not respect the legal limit of adding cane sugar established by law.
Keywords: Cocus nucifera L.; beverage; isotope analysis; law; fraud